Aislamiento de Vibrio cholerae no -01 en el Golfo de Nicoya, Costa Rica - Antillón G., Florencia (1992)
In a bacteriological study on samples of bivalves, mud and surface waters from fue Gulf of Nicoya, Costa Rica, 18 strams of non-01 Vibrio cholerae and 50 of V. mimicus were isolated. The samples were ennched in alkaline peptone water, and streaked on MacConkey and inositol-brilliant green bile agars. Biochernical and serological tests were used for their identification. Bofu species were isolated from all sampling sites (Lepanto, Jicaral and Puntarenas) with either of fue two agar media, even fuough fuese were not specific for vibrios.